Evaluating physical education and sports curriculum from the secondary stage as perceived by physical education teachers - سفيان قسيمي (Université de M'sila, 2022)
the study aims at identifying the reality of physical education curriculum for the secondary stage as perceived by teachers of physical and sports education ,Moreover findings if there are any significant statistical differences attributed to (scientific qualification ,seniority in teaching).To achieve the objectives of the study, the researcher used the analytical descriptive method, in the selected study sample, there are 146teachers of physical education The researcher constructed the following research tools Questionnaire addressed to the teachers of(70) paragraphs ,distributed among four areas: objectives ,content ,Teaching Methods, Assessment methods. The results of the study showed there is no statistically significant difference between teachers answers Averages in direction of physical education curriculum due to study variables (scientific qualification, seniority in teaching). the researcher has recommended 􀀁
Keywords: Evaluation, curriculum of physical education and sport,􀀁professor of E. p. s, secondary stage.􀀁